HEMODIAPERFUSION IN LEPTOSPIROSIS - Galya I. Gancheva (Peytchinski Publishing, 2005)
Comparatively have been studied laboratory parameters in severe cases of leptospirosis divided in two groups - with and without hemodiaperfusion (HD). The dynamical investigations of blood urea nitrogen (BUN), serum creatinine, and serum bilirubin levels reveal that hemodiaperfusion markedly decreases the levels of nitrogen parameters and is non effective for serum bilirubin. Hemodiaperfusion in oliguric phase of the acute renal failure of leptospirosis prevents brain edema and lung edema - significant tanatogenic factors.